Ферорезонансні процеси та захист трансформаторів напруги в електричних мережах 6-35 кВ - Масляк, Роман Ярославович (Національний університет "Львівська політехніка", 2014)
Дисертація присвячена дослідженню ферорезонансних процесів. Встановлено вплив зміни параметрів мережі на можливість виникнення таких процесів. Запропоновано узагальнену однофазну розрахункову модель, на якій було проведено попередній аналіз причин виникнення ФРП та способи його недопущення або зриву. Створено трифазні розрахункові моделі мережі з різними типами трансформаторів напруги різних класів напруг та встановлено діапазони ємнісних струмів мережі для кожного з них, за яких можливе виникнення ФРП у мережі. Встановлено зони величин гасильних опорів від ємностей мережі для кожного з них, за яких відбудеться гарантований зрив ФРП. Запропоновано систему захисту ТН для підстанцій з двома секціями (системами) шин та встановлено ефективність її роботи. Диссертация посвящена исследованию феррорезонансных процессов. Исследовано влияние изменения параметров сети на возможность возникновения таких процессов. Предложено обобщенную однофазную расчетную модель, на которой был проведен быстрый предварительный анализ причин возникновения ФРП и способы его недопущения или срыва. Созданы трёхфазные расчётные модели сети с разными типами трансформаторов напряжения разных классов напряжений и установлены диапазоны ёмкостных токов сети, при которых возможно возникновение ФРП сети. Установлены зони величин гасительных сопротивлений от ёмкостей сети для каждого из них, при которых состоится гарантированный срыв ФРП. Предложена система защиты ТН для подстанций с двумя секциями шин и показана эффективность её работы. The dissertation is devoted to research the ferroresonance processes (FRP) in networks with low earth-fault currents. The causes of it occurrence are analyzed. Previous researches of this problem are reviewed. The existing ways and methods of protection are analyzed. The influence of changing network parameters on the possibility of their occurrence is researched. The universal single-phase scheme is designed. At this scheme was conducted the previous analysis of the reasons of FRP occurrence and its development in network. The possibility of it prevention or disruption is researched. The effect of network parameters on the rate of the voltage saturation transformer (VT) is defined. The change impact in characteristic of VT magnetization on the possibility of FRP occurrence is researched. The values range, for which is possible its occurrence are set. The possible methods to prevent FRP are researched. The values of preventive resistors are defined. The possibility of it prevention by changing network capacity is researched. The specified three-phase mathematical models of network with different electromagnetic VT types of different voltage classes are created. Researches of simultaneous parallel operation of voltage transformers of different types were conducted at the first time. The specified ranges of capacitive currents (capacities) network, by which may FRP occur in network are set. It is proved that the most effective method of protection for today is extinguishing resistance connection in the winding disconnected triangle. Тhe specified ranges of network capacities by which FRP may occur for all of VT types are defined. Dependencies of extinguishing resistances on the network capacities for all VT types are set. The occurrence of subharmonic oscillations caused by the creation of a consistent resonant circuit between the power transformer and the interfacial network capacitances at not full-phase modes of the network is considered. A possibility of damage as power transformers and voltage transformers here is proved. By results of researches, there are constructed the dependences of maximal values of a capacity earth-fault on a capacity of power transformers as ТМ, which can cause the FRP occurrence. The possibility of FRP disruption by changing the network capacity is researched. There are investigated FRP, arising from non-permanent DHA communication. The system of VT protection for substations with two sections (systems) of tires is offered. Its structural diagram is shown and a principle of it work is explained. The mathematical model of the real electric network is created. Efficiency of her work is proved. The measures are considered and the system of protecting from the abnormal shutdown of grounding transformer with the turned on the extinguishing reactor is offered. A structural protection scheme is given and a principle of it work is explained. The currents in VT neutrals are analyzed and a new system of protection from FRP that works via Wi-Fi sensors is proposed. A structural diagram of such system is presented and a principle of it work is explained.
Феррорезонансные процессы и защита трансформаторов напряжения в электрических сетях 6-35 кВ
The ferroresonance processes and the voltage transformers protection in electrical networks 6-35 kV
Keywords: ферорезонансні процеси; електромагнітні трансформатори напруги; пристрій захисту; розрахункова модель; феррорезонансные процессы; электромагнитные трансформаторы напряжения; устройство защиты; расчётная модель; ferroresonance process; electromagnetic voltage transformers; protecting devise; mathematical modelling